FATORES QUE CONTRIBUEM PARA O DESENVOLVIMENTO DA GOVERNANÇA TRIBUTÁRIA: UM ESTUDO DE CASO SOBRE A ESTRUTURAÇÃO DA ADMINISTRAÇÃO TRIBUTÁRIA DA PETROBRAS - Castro, Hélder Uzêda (2013)
The aim of this study was to investigate factors that contribute to the development of tax governance in a large company. The method of case study was chosen for this investigation, being applied to the structuring of the tax administration of Petrobras; this corporation was chosen because it is the largest tax contributor in Brazil. The undertaking of this study included analyses on documents and records of the studied corporation; direct in loco observation; and interviews, individual and with groups of two or three of the professionals who were involved in the process, and also with those who had information that was relevant to the understanding of the object of study. At the end of this study it was acknowledged that: The structuring of the tax management of the company brought efficiency gains, resulting in the optimization of financial resources; Corporate Governance, focused on the taxes, contributes to the development of Tax Governance; in order to meet the requirements of the Tax Authorities, the studied company makes intensive use of the information technology in the process of tax implementation; the execution of the tax processes in the structure of Shared Services Center is still a challenge, because such processes are not transactional, and, finally; the establishment of boundaries between the areas working in the tax activity played a key role in the development of the Tax Governance adopted by the corporation.